2021
DOI: 10.25165/j.ijabe.20211404.6821
|View full text |Cite
|
Sign up to set email alerts
|

Development status and trend of agricultural robot technology

Abstract: In the face of the contradiction between the increasing demand for agricultural products and the sharp reduction of agricultural resources and labor force, agricultural robot technology is developing explosively on the basis of decades of technical and industrial exploration. In view of the complexity and particularity of the development of agricultural robot technology, it is of great value to summarize its development characteristics and make reasonable judgments on its development trend. In this paper, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 96 publications
(133 reference statements)
0
16
0
Order By: Relevance
“…Efficient software analysis developed for agriculture/forestry research will improve smart agriculture. For example, regression algorithms based on the least form algorithm can predict plant growth, while similar linear or non-linear analytical functions can also correlate plant biomass data [60,84,85,86] .…”
Section: Non-destructive Extraction and Precision Requirements Of Datamentioning
confidence: 99%
“…Efficient software analysis developed for agriculture/forestry research will improve smart agriculture. For example, regression algorithms based on the least form algorithm can predict plant growth, while similar linear or non-linear analytical functions can also correlate plant biomass data [60,84,85,86] .…”
Section: Non-destructive Extraction and Precision Requirements Of Datamentioning
confidence: 99%
“…In the case of picking valuable fruits with robots, the technology is close to being implemented in a commercial product in the near future [101]. In [102], the agricultural robots have been classified based on the type of application. The results showed that navigation systems, robot-crop interactions, and agronomy-robot fusion are scientifically important to promote advances in agricultural robot technology.…”
Section: Research Challenges and Opportunitiesmentioning
confidence: 99%
“…Spanish AGROBOT Robotics [123] developed a strawberry harvesting robot for high-monopoly and rack cultivation that employed 24 robotic arms arranged on six linear module units, each with a short-view integrated color and infrared depth sensor and image processing unit, to determine the ripeness of the strawberries to be harvested, and which used stem-breaking clamping to harvest the strawberries to avoid damage. However, since a dual-arm cooperative mode imposes higher requirements on the manipulator configuration, canopy space, and collaborative control [124,125], further exploration is needed of whether dual-arm harvesting robots are the optimal future direction of harvesting robotics development.…”
Section: Robot Arms Applied In Agricultural Robotsmentioning
confidence: 99%